Linking Local and Global Social Movements and the Anti-ADB Campaigns: From Chiang Mai to Samut Prakarn - Encarnacion Tadem, Teresa S. (Kasarinlan: Philippine Journal of Third World Studies; Vol 23 No 1 (2008): Contentious Politics, 2008)
This paper examines the factors which facilitated the linking of transnational social movements with local social movements in Thailand with regards to their anti-Asian Development Bank (ADB) campaigns. These transnational social movements include international nongovernment organizations (INGOs), such as the Bank Information Center, International Rivers Network, Greenpeace Southeast Asia, and NGO Forum on the Asian Development Bank (ADB) in assisting the villagers of Klong Dan and social movements in Thailand in pressuring the ADB to look into their allegations concerning the Bank’s Samut Prakarn Wastewater Management Project (SPWMP). Two of the major issues raised were that the project was environmentally unfriendly and that there was corruption involved in its implementation. A major objective of the INGOs and local social movements was for the ADB to investigate the project based on its established rules and procedures for ascertaining transparency, accountability, and good governance. The paper shows how INGOs played a substantive role in assisting as well as supplementing the efforts of the social movements in this regard. There were, however, also limitations to what the INGOs can do particularly with regard to dealing with the local politics vis-à-vis the SPWMP and the dynamics among the INGOs and between the local, Thai social movements and the INGOs. The efforts of local and international social movements were also supported by local political conditions which contributed to the successful anti-ADB campaigns. External factors also reinforced the advocacy of local and international social movements against the ADB among which were the emergence of the anti-globalizations movements in general and the advocacy of international as well as regional NGOs against ADB projects and policies in general.
Keywords: international nongovernment organizations; social movements; Asian Development Bank; Samut Prakarn Wastewater Management Project; Thailand